Highly diversified coronaviruses in neotropical bats - Spínola, Romeo (2013)
Bats host a broad diversity of coronaviruses (CoVs), including close relatives of human pathogens. There is only limited data on neotropical bat CoVs. We analysed faecal, blood and intestine specimens from 1562 bats sampled in Costa Rica, Panama, Ecuador and Brazil for CoVs by broad-range PCR. CoV RNA was detected in 50 bats representing nine different species, both frugivorous and insectivorous. These bat CoVs were unrelated to known human or animal pathogens, indicating an absence of recent zoonotic spill-over events. Based on RNAdependent RNA polymerase (RdRp)-based grouping units (RGUs) as a surrogate for CoV species identification, the 50 viruses represented five different alphacoronavirus RGUs and two betacoronavirus RGUs. Closely related alphacoronaviruses were detected in Carollia perspicillata and C. brevicauda across a geographical distance exceeding 5600 km. Our study expands the knowledge on CoV diversity in neotropical bats and emphasizes the association of distinct CoVs and bat host genera.